Physical Vulnerability of Coastal Zone of Sidoarjo Distric to Potential Impact of Sea Level Rise due to Climate Change - Hermawan Meidy Kurnianto; Mohammad Bisri; Maftuch Maftuch (Indonesian Journal of Environment and Sustainable Development, 2018)
Climate change impact such as an increased on the intensity and the frequency of rainfall in the oceans cause sea level rise which then impacts the water surface in the river. This condition has an impact on fishery cultivation in coastal areas. People in Sidoarjo regency are increasingly affected by the alteration of water surface in coastal areas. Sidoarjo region is divided into 5 sub-development areas of one of the 5 sub-regional development units (SSWP V) which are a coastal area with aquaculture fisheries aquaculture economic center. Physical parameter indicators including secondary data and spatial map (GIS) were conducted. The result showed that 4 villages with the highest physical vulnerability of Sidoarjo Regency to the impact of climate change including Kalanganyar Village, Kupang, Tambak Kalisogo and Permisan. Keywords: Coastal, Exposure, GIS, Sea level rise